Enhanced bioavailability of danazol nanosuspensions by wet milling and high‑pressure homogenization - Kanthamneni, Naveen; Valiveti, Satyanarayana; Patel, Mita; Xia, Heather; Tseng, Yin‑Chao (International Journal of Pharmaceutical Investigation)
Introduction: The majority of drugs obtained through synthesis and development show poor aqueous solubility and dissolution velocity, resulting in reduced bioavailability of drugs. Most of these problems arise from formulation-related performance issues, and an efficient way to overcome these obstacles and to increase dissolution velocity is to reduce the particle size of drug substances to form drug nanosuspensions. Materials and Methods: Danazol nanosuspensions were prepared by wet milling (WM) and high-pressure homogenization (HPH) methods. The nanosuspensions obtained using these fabrication methods were analyzed for their particle size, surface charge, and the crystallinity of the product was assessed by X‑ray diffraction (XRD) and differential scanning calorimetry techniques. To determine in vitro and in vivo performances of the prepared nanosuspensions, dissolution velocity, and bioavailability studies were performed. Results: Particle size and zeta potential analysis showed the formation of nanosized particles with a negative charge on the surface. XRD depicted the nanocrystalline nature of danazol with low diffraction intensities. With increased surface area and saturation solubility, the nanosuspensions showed enhanced dissolution velocity and oral bioavailability in rats when compared to the bulk danazol suspension. Conclusions: The results suggest that the preparation of nanosuspensions by WM or HPH is a promising approach to formulate new drugs or to reformulate existing drugs with poorly water-soluble properties.
Keywords: Danazol; high-pressure homogenization; nanosuspensions; wet milling